Lived Experiences of Women Navigating End-of-Life Caregiving and Parenting During the COVID-19 Pandemic - Junhee Baek; Faye Ajmera; Paige Chu; Eryn Tong; Sally Bean; Breffni Hannon; Elie Isenberg-Grzeda; Madeline Li; Gary Rodin; Debbie Selby; Camilla Zimmermann; Sarah Hales; et al. (Qualitative Health Research, 2026)
The COVID-19 pandemic intensified the burden on informal caregivers, particularly those with dual caregiving roles. This grounded theory study explores the lived experiences of women who simultaneously cared for a hospitalized family member at the end of life and for minor children during the pandemic. We aimed to examine how the intersection of these roles influenced women’s experiences during caregiving and into bereavement. We analyzed 11 qualitative interviews with bereaved women caregivers in Toronto, Canada, who simultaneously cared for minor children and a dying family member during the COVID-19 pandemic. Our findings reveal a core category of Caregiving and Grieving in Survival Mode, and show that these caregivers (i) often neglected their own needs due to being pulled into numerous responsibilities; (ii) perceived their children as both sources of motivation yet as adding emotional burden to their caregiving; and (iii) felt isolated due to the need for human touch, making small compassionate gestures from healthcare providers seem meaningful. These findings highlight the compounded challenges of dual caregiving and bereavement under crisis conditions and identify a critical need for tailored support for the vulnerable population of dual caregivers.